Search for New Antioxidants and Other Related Bioactive Compounds from Zingiberaceous Species - Mohamad, Habsah (2002)
Thirty-one species from Zingiberacea family were screened for their antioxidant (FTC method), antimicrobial (disc diffusion method), and antitumour promoting (EBV EA assay method) activities. Three species, A lpinia zerumbet, A lpinia rfflesiana and Etlingera elatiar, were selected for further study, based on their promising preliminary biological activities. Five known compounds were isolatpd hom the rhizomes of Alpinia zerumbet, namely S,6-dehydrokawain, flavokawin B, l,7-diphenyl-Shydroxy- 6-heptene-3-one, (-)-pinocembrin, and a mixture of stigmasterol and β-sitosterol. From the fruits of Alpinia raffiesiana, seven compounds were isolated, namely 5,6-dehydrokawain: flavokawin B, l,7-diphenyl-5- hydroxy-6-heptene-3-one, (-)-pinocembrin, cardamonin, (-)-pinostrobin, and 2',3',4',6' -tetrahydroxychalcone. This is the first report on the isolation of 2',3',4',6' -tetrahydroxychalcone from Alpinia.